Using Bankruptcy to Reduce Foreclosures: Does Strip-down of Mortgages Affect the Supply of Mortgage Credit? - Wenli Li; Ishani Tewari; Michelle White (Center for Economic Studies and ifo Institute (CESifo), 2014)
We assess the credit market impact of allowing mortgage “strip-down” as a foreclosure-prevention measure, where strip-down reduces the principal of underwater residential mortgages to the current market value of the property for homeowners in Chapter 13 bankruptcy. Our identification is provided by a series of U.S. court decisions that introduced strip-down in parts of the U.S. and a Supreme Court ruling that abolished it. We find that the Supreme Court decision led to a small, short-term reduction in mortgage interest rates and a small, short-term increase in mortgage approval rates, but no long-term effects, and the circuit court decisions did not consistently affect mortgage terms. These results suggest that strip-down would be an effective foreclosure-prevention program, because it would have only small and transient effects on the supply of mortgage loans.
Keywords: K35; 330; mortgage; foreclosure; credit market; credit supply; strip-down